2005
DOI: 10.1007/s10620-005-2480-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production by Intestinal Intraepithelial Lymphocyte Subsets in Celiac Disease

Abstract: One of the earliest signs of mucosal immune activation in celiac disease (CD) is an increase in the intraepithelial lymphocyte (IEL) count in the small intestinal epithelium. Though most of those IELs express T cell receptor (TcR)-alphabeta chains, CD is characterized by an increase in TcR-gammadelta+ IELs and by the loss of CD3- IELs. There is currently little evidence that these changes in IEL subset distribution are of relevance in the pathogenesis of CD. We aimed to determine the pattern of cytokine produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
5
19
0
1
Order By: Relevance
“…In addition, it has been demonstrated that gliadin can induce T H 17-polarizing cytokines-for example, IL-1beta and IL-23 production in peripheral blood monocytes-providing a possible causative link between gluten exposure and T H 17 cell expansion in CD. Unlike NCGS patients, CD patients show increased levels of adaptive immune markers in the small intestinal mucosa, triggered by DQ2 DQ8-bounded tTG-deamidated gluten peptides and associated with T H 1 and T H 17 clone activation and T H 1-and T H 17-associated cytokine production, including IFN-gamma, IL-17A, IL-6 (pleiotropic cytokine promoting differentiation and function of T H 17 cells), and IL-21 (also related to T H 1 and T H 17 cell pathology) [63][64][65][66][67][68][69].…”
Section: Innate Versus Adaptive Immunitymentioning
confidence: 99%
“…In addition, it has been demonstrated that gliadin can induce T H 17-polarizing cytokines-for example, IL-1beta and IL-23 production in peripheral blood monocytes-providing a possible causative link between gluten exposure and T H 17 cell expansion in CD. Unlike NCGS patients, CD patients show increased levels of adaptive immune markers in the small intestinal mucosa, triggered by DQ2 DQ8-bounded tTG-deamidated gluten peptides and associated with T H 1 and T H 17 clone activation and T H 1-and T H 17-associated cytokine production, including IFN-gamma, IL-17A, IL-6 (pleiotropic cytokine promoting differentiation and function of T H 17 cells), and IL-21 (also related to T H 1 and T H 17 cell pathology) [63][64][65][66][67][68][69].…”
Section: Innate Versus Adaptive Immunitymentioning
confidence: 99%
“…Hallmarks of coeliac enteropathy include an early rise of intestinal intraepithelial lymphocytes (IEL), followed by crypt hyperplasia and villous atrophy, in response to oral gluten intake [1].…”
Section: Introductionmentioning
confidence: 99%
“…Besides IFN-γ also for example IL-2 and TNF-β mRNA expression have been observed in biopsies from active celiac patients [91] . In contrast, Th2-associated IL-4 is found equally expressed in patients as in controls [89,[91][92][93] .…”
Section: Celiac Diseasementioning
confidence: 86%
“…A trend towards a superior accumulation of IFN-γ in vivo [89] promoting inflammatory effects and a non-proliferative activation of CD4 + lamina propria T cells, especially by activation of Th1-like cells secreting IFN-γ [90] have been shown by gluten. Besides IFN-γ also for example IL-2 and TNF-β mRNA expression have been observed in biopsies from active celiac patients [91] .…”
Section: Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation